Consumers acceptance of artificial intelligence Virtual Try-On systems when shopping apparel online - Almeida, Maria Inês Gouveia de (2021)
Artificial Intelligence is a technology that is present in most of each of us today daily lives. Often, interactions occur unconsciously between individuals and technology. Since it is a technology that is increasingly present in people's daily lives, it is frequent to find and apply it in many business areas, one of which being the virtual retail world. It is in this way that Artificial Intelligence becomes relevant for companies that want to gain by competitive advantage. One of the ways that companies can use and apply Artificial Intelligence is undoubtedly through better understanding of their consumers, establishing a relationship of empathy and understanding out from that of their competitors offering unique and personalized experiences, based on individual needs. One of the ways to provide this virtual experience to consumers is through Virtual Try-On. This investigation seeks to understand the current state of consumer acceptance in relation to Virtual Try-On systems in the online clothing industry through the analysis of 5 parameters that intend to evaluate first the consumers' acceptation and then their behavioral intentions. For this, 5 independent variables were chosen, Perceived Usefulness, Perceived Ease of Use, Perceived Time Consumption, Perceived Accuracy and Ethical Concerns. The study of these variables was further developed through an online questionnaire. After analyzing the results, it was concluded that, in general, consumers have a positive attitude towards the use of Virtual Try-On, and consequently, their behavioral intention is also positive, thus being able to affirm that consumers tend to accept this technology.